New Records of Aphid Species Caught in Water Yellow Traps in Greece - Lykouressis, D.P.; Taylor, M.; Tsitsipis, J.A.; Katis, N. (ENTOMOLOGIA HELLENICA, 1992)
A number of yellow Moericke water traps were placed in Cotton, tomato, tobacco, potato, squash and maize fields in Boiotia, Thessalia, Macedonia and Aitoloakarnania from June to the end of 1992. From a limited number of trip captures examined, fifty nive aphid species were identified of which twenty species arc new records for Greece.